Extraction of Cardamom Seeds Using the Microwave Assisted Extraction (Mae) Method and Phytochemical Testing - Latifasari, Nurul; Raharditya, Carantia; Wulandari, Devi; Raharja, Giovani; Lestari, Diandra Citra (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
Cardamom (Amomum cardamomum) is a plant from the Zingiberaceae family which is used as a spice and medicine. Productivity in Indonesia reaches 124,766 tonnes per year, with exports increasing to 10,462 tonnes in 2021. Cardamom seeds contain bioactive compounds such as phenols, tannins, terpenoids, flavonoids and sterols which have antioxidant and antibacterial properties. To maximize its use, extraction of bioactive compounds from cardamom seeds needs to be carried out, and the Microwave Assisted Extraction (MAE) method is considered more efficient than conventional methods. This study aims to determine the effect of the type of solvent (polar, semi-polar and non-polar) and the length of extraction time using the MAE method on the content of bioactive compounds (flavonoids, phenols, tannins, alkaloids and saponins) in cardamom seed simplicia to determine the optimal extraction combination. In this research, cardamom seeds were extracted using various types of solvents (aquades, ethyl acetate, N-hexane) and extraction times (5, 7, 9 minutes). The results showed that the MAE method was effective for extracting phenolic compounds and alkaloids, but failed to identify flavonoids, tannins or saponins. Tests show that extraction time influences the extraction results of bioactive compounds.